2023
DOI: 10.1111/pbi.14001
|View full text |Cite
|
Sign up to set email alerts
|

Artificial nanovesicles for dsRNA delivery in spray‐induced gene silencing for crop protection

Abstract: Spray-induced gene silencing (SIGS) is an innovative and eco-friendly technology where topical application of pathogen gene-targeting RNAs to plant material can enable disease control. SIGS applications remain limited because of the instability of RNA, which can be rapidly degraded when exposed to various environmental conditions. Inspired by the natural mechanism of cross-kingdom RNAi through extracellular vesicle trafficking, we describe herein the use of artificial nanovesicles (AVs) for RNA encapsulation a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(21 citation statements)
references
References 61 publications
0
21
0
Order By: Relevance
“…This study shows promising results for SIGS. However, the stability and duration of the silencing are limited due to RNA instability/degradation under environmental conditions (Hoang et al, 2022; Niño-Sánchez et al, 2022; Qiao et al, 2023). Re-applying dsRNAs regularly would be feasible in the field and might help to overcome the issues related to the loss of efficacy over time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study shows promising results for SIGS. However, the stability and duration of the silencing are limited due to RNA instability/degradation under environmental conditions (Hoang et al, 2022; Niño-Sánchez et al, 2022; Qiao et al, 2023). Re-applying dsRNAs regularly would be feasible in the field and might help to overcome the issues related to the loss of efficacy over time.…”
Section: Discussionmentioning
confidence: 99%
“…Although we demonstrated that recurring dsRNAs applications improve the efficiency and durability of SIGS, we did not achieve complete disease protection or control. The use of various types of nanocarriers such as artificial vesicles (Qiao et al, 2023), clay nanoparticles (BioClay TM ) (Mitter et al, 2017; Niño-Sánchez et al, 2022), or carbon-based (Wang et al, 2023) among others, can enhance RNA stability and uptake efficiency by the pathogens. Furthermore, it has also been shown to increase the protection window against fungal pathogens, viruses and insects (Jain et al, 2022; Mitter et al, 2017; Mosa and Youssef, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…However, the silencing effects of these complexes are somewhat limited to the local areas of application (Jiang et al ., 2014; Zhang et al ., 2019; Demirer et al ., 2020; Zhang et al ., 2021; Zhang et al ., 2022). Also, some nanoparticles such as LDH nanosheets and artificial nanovesicles have been shown to facilitate the long-distance transport of dsRNA molecules (Li et al ., 2015; Mitter et al ., 2017; Qiao et al ., 2023). However, it is unknown whether these dsRNA-nanocomplexes can penetrate plant cell membrane, as these studies have primarily focused on investigating their impact on gene expression in insects, fungi, or viruses that infected the experimental plants (Li et al ., 2015; Mitter et al ., 2017; Qiao et al ., 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Also, some nanoparticles such as LDH nanosheets and artificial nanovesicles have been shown to facilitate the long-distance transport of dsRNA molecules (Li et al ., 2015; Mitter et al ., 2017; Qiao et al ., 2023). However, it is unknown whether these dsRNA-nanocomplexes can penetrate plant cell membrane, as these studies have primarily focused on investigating their impact on gene expression in insects, fungi, or viruses that infected the experimental plants (Li et al ., 2015; Mitter et al ., 2017; Qiao et al ., 2023). As shown here, our cBSA/dsRNA nanocomplexes may present a highly useful and more convenient tool that not only enables the delivery of RNA molecules into plant cells but also facilitates their long-distance transport within the plant and systemic silencing effects of target genes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation